Isolation of a Clostridium acetobutylicum strain and characterization of its fermentation performance on agricultural wastes - Al-Shorgani N.K.N.; Yusoff W.M.W.; Kalil M.S.; Hamid A.A.; Mohd Hafez Mohd Isa (Elsevier Ltd, 2024)
Indexed by WOS/Scopus